RESEARCH AND VALIDATION OF GLOBAL MPP IN THE RELIABILITY ANALYSIS OF COMPOSITE STRUCTURES - Luísa N. Hoffbauer (2018)
The more realistic analysis of structure failures under uncertainties is associated with the use of probabilistic methods. One of the main problems in the structural reliability analysis of composite laminate structures is the possible existence of multiple MPP (Most Probable Failure Point). In this work, we propose a numerical inverse technique for the global MPP search as a function of the anisotropy of the laminated composites. A Bayesian method to estimate the probability of failure based on Monte Carlo simulation performs the results validation. The validation process demonstrates that the proposed methodology is adequate to estimate the probability of failure of the laminated composite structures.